(untitled) (Global Journal of Science Frontier Research, 2019)
A nonlinear mathematical model of acupuncture meridian explains how acupuncture works. It also explains many of the bizarre features observed in clinical acupuncture practice: i/ why the treatment of distant acupuncture points has maximal effect on the organ, ii/ why for children the cure is faster, and iii/ why some patients feel electric current running from the treated acupuncture point in the direction of the acupuncture meridian, iv/ why this electric current can be expected to run in different direction for males and females. The nonlinear mathematical model predicts electric currents and waves must run from each treated acupuncture point in the direction of the acupuncture meridian. Chinese scientists had already measured the electric currents before our model was reported at a conference, but nobody ever spoke about waves. However, after our model predicted that waves must be involved in every acupuncture treatment, Hungarian scientist reported one year later that they experimentally found the waves.